Contemporary Islamic finance innovations, applications, and best practices - Hunt-Ahmed, Karen (Hoboken, N.J. : John Wiley & Sons, 2013)
A comprehensive look at the innovations, applications, and best practices of Islamic finance Islamic-compliant finance is transacted in every major world financial center, and the need for information on the topic in light of its global reach has grown exponentially. As an expert in this field, author Karen Hunt-Ahmed understands the intricacies of this area of the capital markets. Now, along with the help of a number of experienced contributors, she skillfully addresses Islamic finance from the perspective of practitioners, examining issues in wealth management, contract law, private.
Acknowledgments -- Introduction -- Contemporary Islamic economic thought / Mohammad Omar Farooq -- The legal framework of Islamic finance / Cynthia Shawamreh -- Globalization and Islamic finance : flows and consciousness / Karen Hunt-Ahmed -- Islamic science and the critique of neoclassical economic theory / Waleed El-Ansary -- Juristic disagreement : the collective fatw against Islamic banking in Pakistan / Shoaib A. Ghias -- Managing liquidity risk in Islamic finance / Dr. Mohammed Bashir -- Elements of Islamic wealth management / Paul Wouters -- Sukak and the Islamic capital markets : an introduction / Michael J.T. McMillen -- Sharija compliant mutual funds / Monem Salam -- The evolution of shariah compliant indexes and why they outperform conventional indexes over the long term / by Tariq Al-Rifai -- Takaful / Farrukh Siddiqui -- Islamic human resources practices / William Martin -- An integrated islamic poverty alleviation model / Ali Ashraf, Kabir Hassan -- How does an Islamic microfinance model play the key role in poverty alleviation? : the European perspective / Sabur Mollah, Hamid Uddin -- Case studies -- Islamic finance in an almost post-crisis and post-revolutionary world -- As in politics, all Islamic finance is local / Mark Smyth -- Stepping forward, backward, or just standing still? : a case study in shifting Islamic financial structures offshore / Umar F. Moghul -- Islamic mortgages / by David Loundy -- Sharia quality rating / Nasir Ali Merchant -- Islamic mutual funds performance in Saudi Arabia / Hesham Merdad, Kabir Hassan -- Sharijah-compliant investment in the United States / John L. Opar -- Risk management in Islamic finance : a shariah analysis of derivatives instruments / Dr. Mohammed Bashir -- Islamic microfinance / Blake Goud -- About the editor -- Index.
Includes indexes.
Print version record and CIP data provided by publisher.
Includes bibliographical references and index.
Keywords: Finance -- Islamic countries; Finance -- Religious aspects -- Islam; BUSINESS & ECONOMICS -- Finance; Finance; Finance -- Religious aspects -- Islam; Islamic countries; Electronic books; Electronic books; Electronic books